Study Skills and Habits of the Students in Tehran Islamic Azad University of Medical Sciences in the Academic Year 20082009 - Ali Nourian; Fereshteh Shah Mohammadi; Seyed-Nouraldin Mousavi Nasab; Azin Nourian (Kerman University of Medical Sciences, 2011)
Background & Objective : The variety and large volume of study materials of Medicine is an important issue and for a good learning adapting adequate study skills and habits is necessary for the students of Medicine A regular study plan as well as following appropriate study skills and habits is of a great importance This study was carried out to investigate study skills and habits of students in Tehran Islamic Azad University of Medical Sciences   Methods : In this descriptive crosssectional study a questionnaire including 27 questions for the assessment of study habits ( time management concentration reading speed note taking and comprehension) was designed based on cook counselling center and after confirming the reliability and validity (α=089) was distributed among medical students Lower mean score showed better study habits In statistical analysis p